Mothers’ perspective on human papillomavirus vaccine in Eastern Turkey - Türker Aras, Ülkü Ayşe; Kırat, Samet; Yendur, Ozge; Yumru, Ayşe Ender (The European Research Journal, 2023)
Objectives: The rates of vaccination with human papillomavirus (HPV) vaccine, which can prevent many cancers, rank the last place when compared to other childhood vaccination rates. The purpose of the present study was to evaluate the knowledge levels of mothers living in our region about HPV vaccine and their perspectives regarding having the vaccine. Methods: The study was conducted between 15 July and 15 August 2022 in the Department of Obstetrics and Gynecology, Faculty of Medicine, Kafkas University with the mothers of 377 girls. The SPSS 21 program was used and p < 0.05 was accepted as significant. Results: No statistically significant differences were detected between the desire of the mother to have her child vaccinated against HPV and the age of her child (p = 0.740), income level of the household (p = 0.590) and the working status of the mother (p = 0.419). There were statistically significant differences between the desire of the mother to have her daughter vaccinated with HPV, the place where the mother lived (p = 0.001), age of the mother (p = 0.037), family type (p = 0.001), number of people living at home (p = 0.027), education year of the mother (p = 0.004), father’s approval for vaccination (p = 0.001), and mother’s hearing about the Smear Test (p = 0.001). Conclusions: Even if the HPV vaccine is given free of charge, there is resistance in mothers to the vaccine. It is necessary to inform mothers about HPV vaccination for their daughters and to make the vaccination more widespread.